Pengaruh Stigma Sosial pada Manajemen Pengobatan Kanker Kolorektal - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing; Romaito Nasution; Milna Sari (Pusat Riset dan Inovasi Nasional, 2025)
This study investigates the impact of social stigma on colorectal cancer treatment management through a meta-analysis of 47 studies involving 12,358 patients. Results demonstrate significant negative correlations between social stigma and both colorectal cancer treatment adherence (r = -0.42, p < 0.001) and patient quality of life (r = -0.38, p < 0.001). More specifically, regression analyses reveal that social stigma predicts 18% of variance in diagnostic delay (β = 0.43, p < 0.001) and 22% of variance in treatment-seeking delay (β = 0.47, p < 0.001). These findings, when compared to Gonzalez and Smith's (2019), reported a weaker correlation (r = -0.29) between social stigma and treatment adherence, identifying a stronger effect between these variables. Furthermore, unlike Lee et al.'s (2020) study focusing on lung cancer, this research specifically demonstrates that colorectal cancer patients experience 23% higher levels of social stigma (d = 0.58, p < 0.01). In the context of intervention, results confirm that community-based interventions can reduce perceived social stigma by 31% (95% CI: 24%-38%), exceeding the effectiveness reported in Courtens (1996) previous study. Finally, mediation analyses confirm that social support mediates 26.2% of social stigma's effect on treatment adherence and 34.2% on quality of life, while coping strategies mediate 21.4% and 26.3%, respectively. These findings underscore the urgency of integrating social stigma reduction strategies into colorectal cancer treatment management protocols to improve treatment outcomes and patient well-being.